Inverse magnetocaloric effect in sol-gel derived nanosized cobalt ferrite - Gopalan, E. Veena; Al-Omari, I. A.; Kumar, D. Sakthi; Yoshida, Yasuhiko; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Applied Physics A-Materials Science & Processing, 2010)
The magnetocaloric properties of cobalt ferrite nanoparticles were investigated to evaluate the potential of these materials as magnetic refrigerants. Nanosized cobalt ferrites were synthesized by the method of sol-gel combustion. The nanoparticles were found to be spherical with an average crystallite size of 14 nm. The magnetic entropy change (Delta S (m)) calculated indirectly from magnetization isotherms in the temperature region 170-320 K was found to be negative, signifying an inverse magnetocaloric effect in the nanoparticles. The magnitudes of the Delta S (m) values were found to be larger when compared to the reported values in the literature for the corresponding ferrite materials in the nanoregime.